Timing of mechanical ventilation and its association with in-hospital outcomes in patients with cardiogenic shock following ST-elevation myocardial infarction: a multicentre observational study - Waleed AlHarbi; Mohammed Qutub; Prashanth Panduranga; Jassim Al Suwaidi; Wael Al Mahmeed; Hassan Khan; Sultan Alobaikan; Abdullah Alenezi; Mohammed AlShehri; Abdulrahman Arabi; Amin Daoulah; Awad Abdulrazaq AlQahtani; et al. (BMJ Open)
Objective To evaluate the association between the timing of invasive mechanical ventilation (MV) initiation and clinical outcomes in patients with cardiogenic shock (CS) secondary to ST-elevation myocardial infarction (STEMI).Design Retrospective analysis of a multicentre registry.Setting Data were obtained from the Gulf-Cardiogenic Shock registry, which includes hospitals across six countries in the Middle East.Participants 1117 patients diagnosed with STEMI and CS. Of these, 672 (60%) required MV and were included in this analysis.Primary and secondary outcome measures The primary outcome was in-hospital mortality. Secondary outcomes included comparisons of baseline characteristics, Society of Coronary Angiogram and Intervention (SCAI) shock stage, and clinical parameters among groups based on time to MV.Results Participants were categorised by time from shock diagnosis to MV: early (≤15 min), intermediate (30 min) and late (≥60 min). Median times were 15 min (IQR 10–20), 30 min (IQR 25–35) and 60 min (IQR 45–70), respectively. Baseline characteristics were comparable across groups. Increased delay in MV was associated with a higher mortality risk during the first 60 min post-diagnosis, beyond which the risk plateaued. Delayed MV was an independent predictor of in-hospital mortality (OR 2.14, 95% CI 1.36 to 3.38, p<0.001).Conclusions Early initiation of MV in patients with STEMI complicated by CS was associated with lower in-hospital mortality. These findings highlight the importance of timely respiratory support, warranting further investigation in prospective or randomised controlled studies.